2015
DOI: 10.4103/0974-9233.151975
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and histopathological characteristics of corneal stromal dystrophies in Saudi Arabia

Abstract: Purpose:The aim was to determine the frequency and describe the main histopathologic features of corneal stromal dystrophy in Saudi Arabia.Methods:A single-center, retrospective analysis of 193 corneal specimens diagnosed with stromal dystrophy. All samples were retrieved from the Histopathology Department at King Khaled Eye Specialist Hospital over a 10-year period (2002 to December 31, 2011). Cases of stromal dystrophy undergoing keratoplasty were included in the study. Routine histopathologic stains and spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 13 publications
(20 reference statements)
1
12
0
Order By: Relevance
“…The identified known mutations have been observed among patients from several populations included India Saudi Arabia, Korea, Egypt, Japan, America and France [2,3,1517,18,23]. This additionally supports our findings showed a high degree of mutational heterogeneity among the patients studied.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…The identified known mutations have been observed among patients from several populations included India Saudi Arabia, Korea, Egypt, Japan, America and France [2,3,1517,18,23]. This additionally supports our findings showed a high degree of mutational heterogeneity among the patients studied.…”
Section: Discussionsupporting
confidence: 78%
“…Interestingly, we have identified 6 novel mutations in six MCD patients and 11 different known mutations in 38 patients. Previous studies have shown in Saudi Arabian and South Indian population that the prevalence of MCD is high; most probably due to the higher frequency of consanguineous marriage in these ethnic population [2,3]. In our current study, out of 55 families studied, we have also analysed 30 south Indian families with consanguineous marriage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding is in line with previously reported rates in Saudi Arabia. 9 , 36 , 37 Recently Alzuhairy et al, 37 have shown that the corneal stromal dystrophy distribution in Saudi Arabia included macular corneal dystrophy in 93.26%, granular corneal dystrophy in 4.66% and lattice corneal dystrophy in 2.07%.…”
Section: Discussionmentioning
confidence: 99%